2017
DOI: 10.1016/s0140-6736(17)32155-4
|View full text |Cite
|
Sign up to set email alerts
|

Guided de-escalation of antiplatelet treatment in patients with acute coronary syndrome undergoing percutaneous coronary intervention (TROPICAL-ACS): a randomised, open-label, multicentre trial

Abstract: SummaryBackground Current guidelines recommend potent platelet inhibition with prasugrel or ticagrelor for 12 months after an acute coronary syndrome managed with percutaneous coronary intervention (PCI). However, the greatest antiischaemic benefit of potent antiplatelet drugs over the less potent clopidogrel occurs early, while most excess bleeding events arise during chronic treatment. Hence, a stage-adapted treatment with potent platelet inhibition in the acute phase and de-escalation to clopidogrel in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
382
0
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 485 publications
(422 citation statements)
references
References 41 publications
5
382
0
22
Order By: Relevance
“…Further on, switching and especially a de-escalation of DAPT (switching from potent P2Y 12 -inhibitors to clopidogrel) was subject to a number of randomized clinical trials. 716,717 Triggers for DAPT de-escalation include clinical (bleeding events or presumed high bleeding risk) and socio-economic factors. 716 Based on recent results from the randomized TROPICAL-ACS (Testing responsiveness to platelet inhibition on chronic antiplatelet treatment for acute coronary syndromes) trial 717 , an approach of DAPT de-escalation guided by platelet function testing may be considered in ACS patients (NSTE-ACS and STEMI) as an alternative to 12 months potent platelet inhibition, especially for patients deemed unsuitable for maintained potent platelet inhibition.…”
Section: Peri-interventional Treatmentmentioning
confidence: 99%
“…Further on, switching and especially a de-escalation of DAPT (switching from potent P2Y 12 -inhibitors to clopidogrel) was subject to a number of randomized clinical trials. 716,717 Triggers for DAPT de-escalation include clinical (bleeding events or presumed high bleeding risk) and socio-economic factors. 716 Based on recent results from the randomized TROPICAL-ACS (Testing responsiveness to platelet inhibition on chronic antiplatelet treatment for acute coronary syndromes) trial 717 , an approach of DAPT de-escalation guided by platelet function testing may be considered in ACS patients (NSTE-ACS and STEMI) as an alternative to 12 months potent platelet inhibition, especially for patients deemed unsuitable for maintained potent platelet inhibition.…”
Section: Peri-interventional Treatmentmentioning
confidence: 99%
“…73,74 The randomized TOPIC trial (Timing of Optimal Platelet Inhibition After Acute Coronary Syndrome) showed that in patients who have been event free for the first month after an ACS on a combination of aspirin plus a new-generation P2Y 12 inhibitor, de-escalation to aspirin plus clopidogrel was associated with reduced bleeding complications, mostly minor. 73 Although this study did not show any differences in ischemic events between groups, play of chance cannot be ruled out given the limited sample size of the trial.…”
Section: De-escalation (Switching From Prasugrel or Ticagrelor To Clomentioning
confidence: 99%
“…The TROP-ICAL-ACS trial (Testing Responsiveness to Platelet Inhibition on Chronic Antiplatelet Treatment for ACS) randomized patients with ACS undergoing PCI to either standard treatment with prasugrel for 12 months or a de-escalation regimen (1 week of prasugrel followed by 1 week of clopidogrel and platelet function testing-guided maintenance therapy with clopidogrel or prasugrel from day 14 after hospital discharge). 74 The trial showed that a strategy of guided de-escalation of antiplatelet treatment was noninferior to standard treatment with prasugrel at 1 year in terms of net clinical benefit. The strategy did not show any increase in ischemic events, although there was a numeric but not statistically significant reduction in bleeding.…”
Section: De-escalation (Switching From Prasugrel or Ticagrelor To Clomentioning
confidence: 99%
“…Bleeding Academic Research Consortium 2 or higher bleeding events were similar between groups. 48 Although costly and time-consuming, early deescalation of antiplatelet treatment guided by platelet function testing may be an alternative approach in some patients. On a similar subject but with no use of platelet function testing guidance, the TOPIC (timing of platelet inhibition after acute coronary syndrome) trial showed that de-escalation from prasugrel or ticagrelor to clopidogrel after 30 days from the ACS may achieve lower bleeding rates than standard therapy with the more potent P2Y12 inhibitors for 12 months.…”
Section: Platelet Testingmentioning
confidence: 99%